2024
DOI: 10.1039/d3qm01290e
|View full text |Cite
|
Sign up to set email alerts
|

High-performance Bi2Se3/MXene/SWCNT heterostructures as binder-free anodes in lithium-ion batteries

Raimonds Meija,
Vitalijs Lazarenko,
Yelyzaveta Rublova
et al.

Abstract: Bi2Se3, MXenes, and SWCNTs are promising potential alternatives to replace the conventional graphite in the anodes of lithium-ion batteries (LIBs) and enhance their performance. However, all these materials have drawbacks,...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 81 publications
(123 reference statements)
0
3
0
Order By: Relevance
“…The voltage of Bi 2 Se 3 @ MXene/Cu decreased more slowly than that of Cu, which was due to the lithiation process of Bi 2 Se 3 @MXene. 62 The Li nucleation overpotential on Bi 2 Se 3 @MXene/Cu (13.3 mV) was lower than that on Cu (19.5 mV) (Figure 6b). In addition, Bi 2 Se 3 @MXene/Cu (18.9 mV) had a Li deposition overpotential lower than that of Cu (26.6 mV).…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…The voltage of Bi 2 Se 3 @ MXene/Cu decreased more slowly than that of Cu, which was due to the lithiation process of Bi 2 Se 3 @MXene. 62 The Li nucleation overpotential on Bi 2 Se 3 @MXene/Cu (13.3 mV) was lower than that on Cu (19.5 mV) (Figure 6b). In addition, Bi 2 Se 3 @MXene/Cu (18.9 mV) had a Li deposition overpotential lower than that of Cu (26.6 mV).…”
Section: Resultsmentioning
confidence: 91%
“…Voltage–capacity curves are presented to investigate the nucleation behaviors of Li on Cu and Bi 2 Se 3 @MXene modified Cu (Bi 2 Se 3 @MXene/Cu) current collectors (Figure a, Figure S25). The voltage of Bi 2 Se 3 @MXene/Cu decreased more slowly than that of Cu, which was due to the lithiation process of Bi 2 Se 3 @MXene . The Li nucleation overpotential on Bi 2 Se 3 @MXene/Cu (13.3 mV) was lower than that on Cu (19.5 mV) (Figure b).…”
Section: Resultsmentioning
confidence: 95%
“…The formation of heterostructures effectively prevents the 2D restacking of Mxene and increases the number of active sites for energy storage. [40][41][42][43][44][45][46] Among them, it can be found that the 2D/2D heterojunctions have been rarely explored for energy storage, particularly using the two emerging 2D materials of Ti 3 C 2 T x and GDY. 47 As reported, the 2D/2D heterojunctions can maximize the enrichment of active sites and have been found to efficiently tune the interfacial electronic properties.…”
Section: Introductionmentioning
confidence: 99%